Water Spinach (Ipomoea reptans Poir) Hydroponic Kratky System at Various Levels of PbSO4 Contamination - Khodijah, Nyayu Siti; Santi, Ratna; Kusmiadi, Riwan; Rismunandar, Ivan (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
Lead (Pb) contamination and types of nutrients in static hydroponic system for growing water spinach are increasingly being studied due to the impact on the food chain. Consequently, the presence of Pb needs to be considered, specifically in fast-growing plant commodities. Alternative nutrient sources that are cheaper and more easily available should be developed and tested for effectiveness in the Kratky hydroponic system. In general, the Kratky hydroponic system runs without electricity and does not use wicks, making it economical and easy to apply in urban agriculture. Therefore, this research aimed to determine the effect of nutrition type and Pb absorption on the growth of water spinach planted in the Kratky hydroponic system. Test plants were planted for 30 days and the research used a 2-factor factorial randomized block design. The Pb concentration was varied at 50 , 100, 150, and 200 mg/L. The plant without Pb was used as control. The nutrition types used were standard hydrophonic (N1) and alternative nutrients containing NPK and Gandasil D (N2). The results showed that nutrition type had a significant effect on plant height, number of leaves, root length, wet and dry weight of shoots and roots, leaf area, shoot root ratio, harvest weight and stem diameter. The ABmix nutrient type (standard hydroponic media) has better performance than alternative nutrient types. There was no growth disturbance due to Pb contamination in the form of PbSO4 . Furthermore, the combination of Pb concentration and nutrient-type treatment did not have a significant effect on the plant’s growth and production except for the number of leaves. The combination of Pb concentration of 50 mg. L-1 and AB mix nutrition provided the best number of leaves.